The effect of a six-month programme of intradialytic cycling on survival and hospitalisations in people requiring haemodialysis: 5-year follow-up of the CYCLE-HD randomised controlled trial - Sherna F. Adenwalla; Hannah M. Worboys; Daniel Lawday; Laura J. Gray; Katherine L. Hull; Darren R. Churchward; Patrick J. Highton; Hannah M. L. Young; Matthew P. M. Graham-Brown; James O. Burton; Daniel S. March (PLoS ONE, 2025)
We have previously shown that a six-month programme of intradialytic cycling (IDC) improved cardiovascular structure and function, it is unclear whether these changes are associated with long-term benefits. The aim of this post-trial analysis was to evaluate a programme of IDC on all-cause mortality, hospitalisations and cardiovascular events at five-years. Mortality and hospitalisation data were collected from Hospital Episode Statistics and death certificates. Models were fitted unadjusted and adjusted for age, sex, diabetes, duration of dialysis, and receiving a kidney transplant. Cox proportional hazard models were used for time-to-event analysis to evaluate all-cause mortality. Hospitalisations were analysed using a negative binomial regression model, and length of stay using a generalised linear model. A composite outcome of time to first cardiovascular event, combining cardiovascular mortality and hospitalisations, was evaluated using a Cox model. There was no evidence of a statistically significant effect of treatment allocation on survival (hazard ratio (HR) 1.09, 95% confidence interval (CI): 0.68–1.76, p = 0.71). After adjustment, results remained non-significant (HR 1.22, 95% CI: 0.74–2.01, p = 0.43). There was no evidence of a significant effect on all-cause hospitalisations for unadjusted (p = 0.20) or adjusted (p = 0.25) models. Similar results are reported for cardiovascular hospitalisations (p = 0.30 and p = 0.17). For time to first cardiovascular event there was no evidence of a statistically significant effect (HR 1.39, 95% CI: 0.79–2.72, p = 0.26). The main findings show no evidence that a six-month programme of IDC affected all-cause mortality, hospitalisations, cardiovascular events, or length of stay in hospital at five-years.